Some Aspects of Internal Security Policy as an Element of the National Security Strategy of the Republic of Serbia - Stajić, Ljubomir; Radivojević, Nenad P; Mirković, Vladan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
The establishment or reorganization of the national security system is always based on certain strategic and legal acts that determine organization, competencies, powers, coordination, cooperation, control and other issues relevant for the work of the subjects of the national security system. These documents must be an expression of the consensus of the relevant actors of a society. The Republic of Serbia passed its first National Security Strategy in 2009, although reforms of the national security system had begun before that. Given the current status of the constitutional reform issues, as well as the announcement of the adoption of a new national security strategy that is expected in the upcoming period, we looked at some general issues of strategic acts as well as practical scope of implementation of the internal security policy conducted in the previous eight years. Also, we introduced new classifications of strategic documents dealing with national security issues and pointed out some issues that need to be taken into account when creating and implementing national security policy. Taking into account the large number of security system subjects in charge of achieving internal security, as well as the scope of this paper, we have only analyzed only some of the adopted strategic and normative legal acts derived from the National Security Strategy. These acts regulate the organization and functioning of the police as an organizational unit of the Ministry of the Interior, and they are concerned with the fight against organized crime.